Experimental Study on Liquid-assisted Nanosecond Laser Processing of Inconel 718 Micropores - Li, Xuri; Sun, Shufeng; Wang, Pingping; Zhang, Fengyun; Wang, Jin; Wei , Tao; Chen, Gongliang; Li, Junbao; Zhu, Yong (International Journal of Mechanical and Electrical Engineering, 2025)
In this paper, the experiment of IN718 superalloy was carried out with the aid of liquid, and the influence of liquid aid on key indexes such as hole taper and diameter of inlet and outlet was systematically analyzed. At the same time, the chemical element composition of the hole wall was detected, and the thickness of oxide layer formed in different environments during machining was studied. Finally, the processing mechanism of IN718 superalloy nanosecond laser drilling under liquid-assisted conditions is discussed. The results show that both water-assisted and liquid-assisted can improve the quality of micropores in different degrees compared with the condition without auxiliary field in air, especially the effect of liquid-assisted is the most significant. Under this condition, the hole taper is reduced by 67%. In addition, with the help of liquid, the content of oxygen element in the pore wall of micropores is greatly reduced, and the element composition is closer to the base material. This study provides important theoretical support and technical optimization direction for nanosecond laser drilling technology.